Integrative Technology for Creating Electronic Educational Resources - Guraliuk, Andrii; Zakatnov, Dmytro; Lapaenko, Svitlana; Ahalets, Inna; Varaksina, Nataliia (International Journal of Engineering Pedagogy, 2023)
To increase the efficiency of using ontologies in the educational process, we have developed the Ontos.xyz resource, which consists of an ontograph editor and a viewer that allows displaying both individual EERs and their collections. The editor allows creating an ontograph that describes the structure of the EER, as well as the ability to assign to each node a context of all types supported by the browser including html-pages, web 2.0 resources, etc. The EER built-in this way allows the integration of data from different sources with the ability to adapt to the conditions of any subject area, regardless of its specifics. Thus, the digital competencies of the EER creators remain relevant, since they do not need to learn new software resources to work with individual ontology concepts (“ontograph nodes”). As a result of our research, we have developed a technology for using the ontological approach to create an EER. For its implementation, the Ontos.xyz resource was developed, which is an ontological graph editor. The ontograph allows for the primary visualization of the EER structure, interpreting its structural elements as nodes (vertices) of the graph, and displaying the logic of transitions between structural elements in the form of directed links. With such an approach, the ontology is some kind of aggregator that ensures the integration of the semantic and technological approaches. Building an EER using the ontological approach requires appropriate technological support in terms of description languages, models, software tools, and systems. The software proposed solution, in contrast to its functional counterparts, focuses on use in the educational process.